2021
DOI: 10.1177/13684302211048885
|View full text |Cite
|
Sign up to set email alerts
|

Changing public opinion about gender activates group threat and opposition to feminist social movements among men

Abstract: Two studies examined whether men’s perception of the declining value of traditional masculinity activates social status, realistic, and symbolic threat, and in turn motivates opposition to feminist social movements. In Study 1, men’s perception that their ingroup is losing value across several social spheres was associated with social status and realistic threat, both of which were associated with opposition to feminist movements. Study 2, an experiment, presented men with public opinion data showing a 30-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…These findings suggest that women might be motivated to support reactionary action for men if they align with the content of their ingroup identity and preserve their traditional worldview. Indeed, recent studies confirm the role of the perceived threat to traditional values, social hierarchy, and symbolic status (among male respondents) as predictors of collective action supporting the status quo and opposition to feminist social movements (e.g., Choma et al, 2020;Rivera-Rodriguez et al, 2021).…”
Section: Collective Action For Other Groups In the Context Of Gendermentioning
confidence: 93%
“…These findings suggest that women might be motivated to support reactionary action for men if they align with the content of their ingroup identity and preserve their traditional worldview. Indeed, recent studies confirm the role of the perceived threat to traditional values, social hierarchy, and symbolic status (among male respondents) as predictors of collective action supporting the status quo and opposition to feminist social movements (e.g., Choma et al, 2020;Rivera-Rodriguez et al, 2021).…”
Section: Collective Action For Other Groups In the Context Of Gendermentioning
confidence: 93%
“…In the face of these threats, some men may exhibit defensive reactions as members of advantaged groups tend to do. For instance, the perception of the declining value of traditional masculinity seems to activate different kinds of intergroup threat (i.e., status, realistic, symbolic) among men, which in turn increases their opposition to feminism (Rivera-Rodriguez et al, 2021).…”
Section: Antifeminism the Far Right And The Men's Rights Movementmentioning
confidence: 99%
“…In an interesting twist, Rivera-Rodriguez, Larsen and Dasgupta (2022) examined how men react when perceiving that masculinity is decreasing in social value, with the implication being that if masculinity devalued, then men in turn will be devalued. Whereas much of the emphasis on gender relations in the literature focuses on traditional versus untraditional women (and their associated promotion vs. resistance), this research points a lens at the perceived role of traditional or nontraditional men in society.…”
Section: Preview Of the Special Issuementioning
confidence: 99%
“…The Special Issue also highlights potential mediators of demographic or power shift effects, providing insights into the mechanisms (or the "why" questions). Understandably, most researchers pursued the notion of threat in its many forms, including status threat, realistic (i.e., tangible) threat (including perceived discrimination against the dominant group), symbolic threat (i.e., nontangible), or moral threat (e.g., Brown, Rucker and Richeson 2022;Domen, Scheepers, Derks and van Veelen 2022;Dover, 2022;Jones et al, 2022;Okuyan & Vollhardt, 2022;Reyna et al, 2022;Rivera-Rodriguez, Larsen and Dasgupta 2022). Most of these endeavors generally found that threats play a significant role in predicting a range of outcomes relevant to solidifying the status quo.…”
Section: Processes Underlying Shift Reactionsmentioning
confidence: 99%